The Role of Artificial Intelligence in Judicial Systems - Žaklina Spalević; Srđan Milosavljević; Dobrivoje Dubljanin; Gradimirka Popović; Miloš Ilić (International Journal of Cognitive Research in Science, Engineering and Education)
The problem we tried to solve relates to the application of artificial intelligence in the legal and judicial system. Given the fact that artificial intelligence (AI) is increasingly taking precedence in various areas of human existence and work, it is an undoubted fact that the legal and judicial systems have not been left out either. It is precisely for this reason that the current state of the use of artificial intelligence in the judicial system, as well as potential new solutions, was first reviewed. In addition to the current one, we focused on the application of artificial intelligence in the legal and judicial system, especially in the domain of decision-making. In this regard, in this paper we propose the use of explainable artificial intelligence, which increasingly takes place when dealing with systems in which the precision and clarity of the parameters on the basis of which a decision is made are of great importance. Looking at the advantages of using explainable artificial intelligence in the decision-making process, one gets the impression that the application of such a model of neural networks can provide the necessary and sufficient conditions for the legal system to accept the use of artificial intelligence in decision-making in the judicial system.